2019
DOI: 10.1088/1674-1056/28/3/037202
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization-direction-dependent inverse spin Hall effect observed in IrMn/NiFe/Cu/YIG multilayer structure

Abstract: The magnetization-direction-dependent inverse spin Hall effect (ISHE) has been observed in NiFe film during spin Seebeck measurement in IrMn/NiFe/Cu/yttrium iron garnet (YIG) multilayer structure, where the YIG and NiFe layers act as the spin injector and spin current detector, respectively. By using the NiFe/IrMn exchange bias structure, the magnetization direction of YIG (M YIG ) can be rotated with respect to that of NiFe (M NiFe ) with a small magnetic field, thus allowing us to observe the magnetization-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…It has been shown that among various CuAu-I type AFMs, IrMn is one of the potential candidate for ISHE studies. Most of the ISHE works on IrMn have been performed with crystalline FM materials like NiFe (Py) [15][16][17]. There have been very few reports of spin pumping with CoFeB/IrMn bilayers [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that among various CuAu-I type AFMs, IrMn is one of the potential candidate for ISHE studies. Most of the ISHE works on IrMn have been performed with crystalline FM materials like NiFe (Py) [15][16][17]. There have been very few reports of spin pumping with CoFeB/IrMn bilayers [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…IrMn exhibits high θ SH within the CuAu-I AFMs. Most of the ISHE works on IrMn have been performed with crystalline FM materials like Py [15][16][17]. There are very few reports of spin pumping with CoFeB/IrMn bilayers [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The ability of controlling transport behavior of electron spin provides a significant way to develop highperformance electronic components. [27][28][29][30][31][32][33][34] Naturally, electron spin can also be utilized in designing molecular logic gates. Specifically, input/output signals of a logic gate can be carried by electron spin (i.e., spin-up and spin-down).…”
Section: Introductionmentioning
confidence: 99%